2017
DOI: 10.1002/jmri.25911
|View full text |Cite
|
Sign up to set email alerts
|

Detection of liver fibrosis using qualitative and quantitative MR elastography compared to liver surface nodularity measurement, gadoxetic acid uptake, and serum markers

Abstract: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1552-1561.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 41 publications
1
19
1
Order By: Relevance
“…Alternatively, MR elastography was used as the reference for fibrosis staging. MR elastography provided the strongest correlation with fibrosis compared with other methods (14,36), with a histologic agreement below 60% (26). Therefore, our results should be interpreted in terms of agreement between the two methods, MR elastography and DW MRI, rather than genuine pathologic fibrosis.…”
mentioning
confidence: 55%
“…Alternatively, MR elastography was used as the reference for fibrosis staging. MR elastography provided the strongest correlation with fibrosis compared with other methods (14,36), with a histologic agreement below 60% (26). Therefore, our results should be interpreted in terms of agreement between the two methods, MR elastography and DW MRI, rather than genuine pathologic fibrosis.…”
mentioning
confidence: 55%
“…Moreover, recently published studies have already shown positive correlations between hepatic T1, T2, and ECV with liver fibrosis in both animal and human models [15,[18][19][20]36]. There are also studies showing positive correlations between T1, T2 mapping parameters and MRE with liver fibrosis, however, without focusing on AIH patients [21,37]. One of the most studied tools for non-invasive assessment of liver fibrosis in patients with AIH is liver stiffness measurement derived by TE (FibroScan) [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, advanced radiologic imaging techniques, such as magnetic resonance elastography (MRE), may provide a more global view of the liver with capability to diagnosis fibrosis non- invasively. In humans, MRE has been shown to provide valuable qualitative and quantitative assessment of liver fibrosis (27–29). From a preclinical standpoint, Huang et al were able to demonstrate a positive correlation between liver stiffness and histologic fibrosis in an 8-pig pilot study investigating the utility of MRE in swine (11); a similar analysis using the Oncopig platform has been initiated.…”
Section: Discussionmentioning
confidence: 99%